Fabrication of a negative PMMA master mold for soft-lithography by MeV ion beam lithography - Puttaraksa N. (2014)
In this study, poly(methyl methacrylate) (PMMA) was investigated as a negative resist by irradiation with a high-fluence 2 MeV proton beam. The beam from a 1.7 MV Tandetron accelerator at the Plasma and Beam Physics Research Facility (PBP) of Chiang Mai University is shaped by a pair of computer-controlled L-shaped apertures which are used to expose rectangular pattern elements with 1-1000 μm side length. Repeated exposure of rectangular pattern elements allows a complex pattern to be built up. After subsequent development, the negative PMMA microstructure was used as a master mold for casting poly(dimethylsiloxane) (PDMS) following a standard soft-lithography process. The PDMS chip fabricated by this technique was demonstrated to be a microfluidic device. © 2011 Elsevier B.V. All rights reserved.